Factors Affecting the Decision to Purchase Arabica Coffee via Online (A Case Study of Online Consumers in Blitar Regency) - Widya Ningsih; Yuhanin Zamrodah; Rima Dewi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the characteristics of Arabica coffee consumers who make online transactions and to see how much influence the given factor has on the decision to purchase Arabica coffee online in Blitar Regency. The execution of this exploration action will be carried out in February 2021 – June 2021 in Blitar Regency. The information-checking strategy used in this exploration is a special examination and various direct examinations of recurrence. Autonomous factor in this research include psychological, personal, social, and cultural. Meanwhile, the dependent variable in this study is the decision to purchase Arabica coffee at online retailers. The results of data analysis found that the X1 (psychological factor) variable was 0.180, X2 (personal factor) was 0.157, X3 (social factor) was 1.012, and X4 (cultural factor) was 0.121 indicating that all variables have positive values. The results of the t-test show that social factors partially influence the purchase decision of Arabica coffee with the online method as shown by the results of t count > t table, namely 5.721 > 2.059. And the F test shows that the decision to purchase Arabica coffee online can be influenced simultaneously by psychological, personal, social, and cultural factors with the calculated F result that is 57.781 > F table which is 2.98.